Predicting recurrence of uterine myoma after carrying out a selective uterine arteries embolization - Marina A. Timchenko; Tatiana A. Kuznetsova; Tatyana I. Morozova; Mariya G. Nikolaeva (IP Berlin A.V., 2022)
Aim. To establish clinic and anamnestic predictors for recurrence of uterine myomas growth after carrying out a selective uterine arteries embolization (s-UAE). Materials and methods. The one-center longitudinal retrospective cohort study including 366 women with symptomatic uterine myoma, after carrying out s-UAE at 20132017. The Control group 315 patients after s-UAE with absolute reduction of blood-circulation and strong remission for 3 years. The main group 51 cases of restoration of clinical symptoms and blood-groove after ultrasonography registered absolute reduction and knocking over of clinical symptoms more than two years period. The median of age of control group patients has made 40 years (95% confidence interval 95% CI 39.041.1), the main 42 years (95% CI 39.043.0). In group of comparison it is carried out the analysis of 103 potential risk factors for uterine myomas relapse after s-EMA. For the correlation between uterine myomas relapse and subset quantitative and qualitative signs the model of the logistic regressions was used with a step-by-step elimination of a sign. Results. Statistically significant risk factors for recurrence of uterine myomas after s-EMA are established: body mass index (BMI) 22,3 (odds ratio OR 4.03); previous plentiful menstrual bleedings (OR 3.56); the previous hormonal therapy (OR 3.06); hypertension (OR 2.58); chronic cystitis (OR 2.18); dyspareunia (OR 2.22); the conglomerate including 23 uterine myomas (OR 1.79); an edge localization of uterine myomas (OR 2.24). Use a logit-models, with inclusion of these specific signs allows to predict uterine myomas growth recurrence after s-EMA in 78.8% cases (95% Cl 0.760.83; р0.0001). Conclusion. At preoperative consultation stage to patients with symptomatic uterine myoma establishment a combination of criteria "body mass index" (BMI)22.3, previous plentiful menstrual bleedings and previous hormonal therapy, assumes to refuse carrying out s-EMA in advantage alternative method of treatment.